Risk Perception Has An Influence On The Decision To Use Action Mobile Banking At Bank Aceh - Fuad, Ammar; Riza, Akmal (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2024)
The decision of customers to utilize the AcTion Bank Aceh application as an alternative platform for conducting daily and business transactions. This study aims to examine the influence of risk perception on customers’ decisions to use AcTion mobile banking. Using a descriptive quantitative method and accidental sampling of 250 respondents in Aceh, the study tested its hypothesis through simple regression analysis. The study’s results demonstrate that the risk perception variable significantly affects the customer decision to use AcTion Bank Aceh.